Exploring the Anti-Inflammatory Activity of Purified Ficus septica Extracts: Insights from In Vitro and In Silico Studies - Arfan Arfan; Ruslin Ruslin; Yamin Yamin; Finantha Annisa; Wa Ode Fitrawati Basrin (JSFK (Jurnal Sains Farmasi & Klinis), 2024)
Ficus septica is a plant that has demonstrated significant potential as an anti-inflammatory agent. This study evaluates the anti-inflammatory activity and molecular mechanisms of compounds from Ficus septica, focusing on their interactions with Bovine Serum Albumin (BSA) and Cyclooxygenase-2 (COX-2). The results show that the purified extracts from Kadia and Batalaiworu exhibited better anti-inflammatory activity, with IC50 values of 32.04 µg/mL and 32.06 µg/mL, respectively, compared to the crude extracts, which had IC50 values of 42.07 µg/mL and 42.44 µg/mL. Despite this, Diclofenac Sodium exhibited a significantly lower IC50 value of 7.99 µg/mL. Computational studies revealed that Genistein had the strongest binding affinity to BSA with a binding energy of -7.52 kcal/mol, comparable to Diclofenac Sodium (-7.51 kcal/mol). Furthermore, Ficuseptine B and Septicine demonstrated strong binding to COX-2, with binding energies of -9.51 kcal/mol and -9.45 kcal/mol, respectively, outperforming Diclofenac Sodium (-8.49 kcal/mol). These findings suggest that compounds from Ficus septica, particularly Genistein, Ficuseptine B, and Septicine, may serve as potential anti-inflammatory agents through their ability to bind to BSA and COX-2.